Hotspot Distribution Analysis In East Kalimantan Province 2017-2019 to Support Forest and Land Fires Mitigation - Nurwita Mustika Sari; Nurina Rachmita; Masita Dwi Mandini Manessa (Research Centre of Inorganic Materials and Complexs, 2020)
Forest and land fires that have occurred in the territory of East Kalimantan Province have caused immediate disaster to the area from year to year and become a global concern in recent years. Hotspots that potentially cause forest and land fires can be detected using satellites such as NOAA-20. The purposes of this study are to analyze the distribution pattern of hotspots in East Kalimantan Province during 2017-2019, identify areas with the highest risk of fires caused by the high intensity of hotspot. The method used in this study is the Nearest Neighbor Analysis and Kernel Density Estimation analysis. The results showed that the distribution pattern of hotspots in East Kalimantan Province during 2017-2019 was clustered with the highest intensity of hotspots were in Berau, East Kutai and Kutai Kartanegara Districts. And from the result of the analysis, the highest number of days has a peak hotspots on September each year. Keywords: forest and land fires, hotspots, Nearest Neighbor, Kernel Density Estimation